问题 解答题
递等式计算.
(1)
7
13
×
3
4
+
3
4
×
6
13
(2)
3
7
÷
7
11
+
4
7
÷
7
11
(3)
12
7
÷(
2
3
-
1
4
(4)
5
9
+
5
9
÷
5
3
(5)
16
5
×
1
2
÷
2
5
(6)36×(
7
9
+
5
6
)÷
29
5
(7)
1
8
×56×
2
7
(8)7×30%(9)
1
6
×6%
(10)12×(
1
2
+
3
4
(11)4÷4%
答案

(1)

7
13
×
3
4
+
3
4
×
6
13

=

3
4
×(
7
13
+
6
13
),

=

3
4
×1,

=

3
4

(2)

3
7
÷
7
11
+
4
7
÷
7
11

=(

3
7
+
4
7
)×
7
11

=1×

7
11

=

7
11

(3)

12
7
÷(
2
3
-
1
4
),

=

12
7
÷
5
12

=4

4
35

(4)

5
9
+
5
9
÷
5
3

=

5
9
+
3
9

=

8
9

(5)

16
5
×
1
2
÷
2
5

=

8
5
÷
2
5

=4;

(6)36×(

7
9
+
5
6
)÷
29
5

=(36×

7
9
+36×
5
6
÷
29
5

=(28+30)÷

29
5

=58÷

29
5

=10;

(7)

1
8
×56×
2
7

=(

1
8
×8)×(7×
2
7
),

=1×2,

=2;

(8)7×30%=2.1;

(9)

1
6
×6%=0.01;

(10)12×(

1
2
+
3
4
),

=12×

1
2
+12×
3
4

=6+9,

=15;

(11)4÷4%=100.

单项选择题
单项选择题 案例分析题